Understanding the Islamic worldview - Abdul Razak, Mohd Abbas; Haneef, Sayed Sikandar Shah (2018)
With the rapid development in the areas of science and technology, many things and ideas come to see the light of the day. Not all that come in the name of progress and development are acceptable to the Muslims who have a unique metaphysical framework (Aqaid) of their own. Nevertheless, without the proper understanding of their Islamic worldview, Muslims are bound to face a lot of challenges from contending ideologies like Secularism, Post-modernism, Liberalism, Humanism, etc. Sad to say, in modern times a small portion from the Muslim community, particularly those who are not well grounded in their understanding of their worldview have gone astray in believing all is well in modern science which mainly comes from the West. This presentation is an endeavor by the research team to highlight what can be adopted and should be discarded in dealing with modern science. This presentation has also highlighted the fact and driven home the message to the Muslim community that a total rejection of modern science is not an ideal thing to do. As such, they have to be meticulously selective in choosing the goodness that comes from modern science.